Groundwater management in transboundary watersheds: vulnerability, environmental risk and climate changes - Antunes, Isabel Margarida Horta Ribeiro (2021)
Apresentação efetuada no "Two days International Workshop on Climate Change Impacts on Groundwater Quality and Health Issues", na India (on-line), 2021